PHARMACOGNOSTIC EVALUATION OF THE LEAF OF Rhus succedanea VAR. HIMALAICA. J. D HOOKER - Khan, Shafqat Ali; Ibrar, Muhammad; -, Barkatullah (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Rhus succedanea is generally traded, distributed and sold in the markets in its crude and raw form. This may have been mixed with adulterants, mismanaged by malpractices and substituted with other closely related drugs having different effect. This study is therefore carried out to authenticate the plant through pharmacogonostic evaluations. Material & Methods: The organoleptic studies were carried through sensory organs i.e size, shape, texrure, odour, etc. Histological studies were conducted by preparing hand slides, mounting the specimen in potato tuber; fluorescence characters were determined through UV and phytochemical screening was investigated using various standard and common methods from relevant literature. Results: Morphologically, the Rhus is a perennial small sized deciduous tree, 5–9 m tall with opposite imparipinnately compound leaves and small grayish yellow flowers born on paniculate inflorescence; locally, called as Rakhkal in Pashto and Kakarsingi in Urdu. The organoleptic evaluation showed leaf had pleasant, aromatic odour and astringent taste. Transverse section of leaf through midrib region was worked out. The anatomy of the midrib has shown to be surrounded by both upper and lower epidermis with multicellular nonglandular trichomes. The leaf was hypostomatic showing anomocytic stomata with average stomatal number 27.1 ± 7.2 and stomatal index 14 ± 3.63. The average vein islet, vein termination and palisade ratios were 13.6 ± 3.04, 10.21 ± 1.92 and 6 ± 2.01 respectively. Leaf powder showed the existance of anomocytic stomata, spirally thickened xylem vessels, non-glandular multicellular and stellate trichomes. Fluorescence study and percent extractive values was also carried out. The phytochemical screening showed the presence of carbohydrates, protein, alkaloids, phenols, flavonoids, terpenoids and anthraquenones, while tannins and fixed oil was not detected. Quantitatively highest amount of alkaloids 16% and flavonoids 19% in leaf was detected. Conclusion: The results of the of the anatomical, organoleptic and physiochemical studies of the powder of leaf will be helpful in standardization of R. succedanea the crude drug.